Creating a response space in multiparty classroom settings for students using eye-gaze accessed speech-generating devices. (1st October 2020) - Tegler, Helena; Demmelmaier, Ingrid; Johansson, Monica Blom; Norén, Niklas
Abstract: Conversation Analysis was used to explore how teachers, personal care assistants, and students organized inclusive multiparty classroom interaction when one of the students in the classroom used an eye-gaze accessed speech-generating device (SGD). Scaffolding and collaborative practices that created a response space for the construction of the eye-gaze accessed SGD-mediated turn were identified and analyzed. The participants were two adolescent students with severe cerebral palsy and intellectual disability who relied on eye-gaze accessed SGDs, and their teachers, personal care assistants, and classmates with intellectual disabilities. The data consisted of 2 hr and 40 min of video recordings collected in the participants' classrooms. Three practices were identified (a) the practice of explicit turn allocation organization and the use of display questions, (b) the practice of locally contingent on-screen scaffolding activities, and (c) the practice of dealing with turn competition by classmates. Teacher and assistant practices differed with regard to the student's access to the vocabulary relevant to answering the teacher's question. The practices were found to create a response space for students using SGDs accessed via eye gaze, thereby ensuring their educational inclusion in the classroom.